ASSESSING HEALTHCARE PROVIDERS’ ACCEPTANCE OF THE HOSPITAL MANAGEMENT SYSTEM IN A PRIVATE HOSPITAL IN SELANGOR, MALAYSIA - Nur Hafizah Sapa; Ruonan Li; Yifei Wang; ZHONGXIN Wang; Zurida Ishak (Global Journal of Public Health Medicine)
Introduction: In the current technological era, the implementation and use of information and communication technology are crucial for productivity and organizational management in the health sector. This study aimed to investigate factors influencing staff acceptance of the Hospital Management System (HMS) using the Unified Theory of Acceptance and Use of Technology (UTAUT) in a private hospital in Selangor, Malaysia. Methods: Semi-structured interviews were conducted with 25 healthcare professionals, including doctors, nurses, and administrative staff, to explore their experiences and perceptions of the HMS. Data collection was performed through interviews and observations and analyzed using thematic analysis with ATLAS.ti. Results: The study identified five key themes influencing HMS acceptance: performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioral intention. Participants emphasized the importance of system reliability, speed, and user-friendly interfaces for efficient workflow. Peer support and a technology-promoting organizational culture positively influenced system use. Comprehensive training and continuous technical support were crucial for user confidence. Despite recognizing the system's benefits, participants highlighted challenges such as inadequate system integration and the need for simultaneous digital and traditional record-keeping. Conclusion: Addressing these issues and tailoring the HMS to meet specific departmental needs can enhance user satisfaction and system effectiveness. The study underscores the importance of understanding user needs and providing robust support systems to facilitate the successful implementation and adoption of HMS in healthcare settings.